Factors Affecting Students’s Intention of Borrowing Consumer Credit in Hanoi - Mai, Nguyen Phuong; Ngoc, Luu Thi Minh; Dzung, Tran Hoang (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 1, 2019)
This research aims at exploring and testing the impact of factors on students’ behavior in borrowing consumer credit in the context of the fast-growing consumer credit market in Vietnam in recent years. Based on the survey results of 225 students in Hanoi, this research shows that both attitude towards credit borrowing and subjective norms affect the intentions of borrowing consumer credit, but the most significant factor is the attitude. In the meantime, attitude is affected by perceived usefulness and perceived ease of use, both of which are reflected in the physical attributes of credit products such as interest, loan payment period, promotion programs, transparent product information, and a quick loan document process. In addition, this research also confirms that students will definitely apply for consumer credit loans when necessary. This is evidence of the open attitude of young customers towards consumer credit, which is a good sign for the expansion of the consumer credit market in Vietnam in coming years. Thus, some implications for consumer financial institutions are proposed in this pape.